Diet Quality and Biomarker Profiles Related to Chronic Disease Prevention: The Multiethnic Cohort Study. (2nd April 2020) - Guillermo, Cherie; Boushey, Carol J.; Franke, Adrian A.; Monroe, Kristine R.; Lim, Unhee; Wilkens, Lynne R.; Le Marchand, Loïc; Maskarinec, Gertraud
Abstract: Objective: To understand how diet quality affects chronic disease etiology, the associations of 4 a priori diet quality indices with blood levels of lipid-soluble micronutrients and biomarkers of inflammation, lipid, and glucose metabolism were examined in 5 ethnic groups. Methods: In a cross-sectional design, the Adiposity Phenotype Study, a subset of the Multiethnic Cohort in Hawaii and Los Angeles, recruited participants of white, African American, Native Hawaiian, Japanese American, and Latino ancestry. A total of 896 men and 910 women completed a validated quantitative food frequency questionnaire and anthropometric measurements and donated a fasting blood sample. Using general linear models, covariate-adjusted mean levels of lipid-soluble micronutrients (total carotenes, lycopene, total tocopherols, total lutein, cryptoxanthins), biomarkers of inflammation (C-reactive protein [CRP], tumor necrosis factor- α ), adipokines (adiponectin, leptin), lipids (total cholesterol, high-density lipoprotein cholesterol [HDL-C], triglycerides), and glucose metabolism (glucose, insulin, homeostatic model assessment of insulin resistance [HOMA-IR]) were computed across tertiles of 4 a priori dietary indices Healthy Eating Index (HEI)-2010, Alternative HEI (AHEI)-2010, alternate Mediterranean Diet (aMED), Dietary Approaches to Stop Hypertension (DASH); trends were evaluated in models with diet quality scores as continuous variables. Results: With better diet quality, levels of carotenes, lutein, cryptoxanthin, adiponectin, and HDL-C were significantly higher ( p trend < 0.01), whereas levels of CRP, leptin, total cholesterol, triglycerides, glucose, insulin, and HOMA-IR were inversely associated ( p trend < 0.05) with diet quality. With the exception of cryptoxanthins and triglycerides, the associations were consistent across ethnic groups. Conclusions: These findings confirm the association between diet quality and nutrition-related biomarkers and support the idea that a high-quality diet positively influences biologic pathways involved in chronic disease etiology across different ethnic groups.